Nursing Care for Babies with Febrile Convulsion in the Child Room - Zulharmaswita; Desi Deswita; Novi Herawati; Abd. Gafar; Syahrum; Yulvi Hardoni; Dwi Putri Adinda (CV. CENDIKIA JENIUS INDONESIA, 2025)
Background: Febrile seizures are a condition of seizures that occur in children caused by fever above 38°C without intracranial infection. Complications can cause children to experience cerebral palsy, motor weakness, slow speech and movement, and cognitive delays. Data from the Children's Room of the Mohammad Natsir Hospital, Solok City in 2022-2023 showed 92 cases of febrile seizures. The purpose of this study was to carry out nursing care for children who experience febrile seizures with a nursing process approach. Methods: The research method used was descriptive with a single case study design. This study was conducted on March 18 - March 20, 2024 with 1 child diagnosed with febrile seizures in the Children's Room of the Mohammad Natsir Hospital, Solok City in 2024. Data collection instruments were, child assessment format, physical examination tools. Data collection methods were interviews, observations, physical examinations, and direct measurements. Results: The results of the assessment were obtained by An. K had a fever, his body felt hot, he had no appetite, the portion he finished was only ¼, and his body temperature was 39°C. Nursing diagnoses obtained, hyperthermia, impaired comfort, and risk of injury. Nursing interventions that can be done, fever management, relaxation therapy, injury prevention. After implementation for 3 days of treatment, the results obtained were improved thermoregulation, increased comfort status, decreased injury levels..